2010
DOI: 10.1530/rep-09-0222
|View full text |Cite
|
Sign up to set email alerts
|

Zona pellucida protein ZP2 is expressed in the oocyte of Japanese quail (Coturnix japonica)

Abstract: The avian perivitelline layer (PL), a vestment homologous to the zona pellucida (ZP) of mammalian oocytes, is composed of at least three glycoproteins. Our previous studies have demonstrated that the matrix's components, ZP3 and ZPD, are synthesized in ovarian granulosa cells. Another component, ZP1, is synthesized in the liver and is transported to the ovary by blood circulation. In this study, we report the isolation of cDNA encoding quail ZP2 and its expression in the female bird. By RNase protection assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Although we did not pursue the discrepancy of the results between the dot blot assay and far-western blotting, we assume that the interaction of the 45 kDa acrosin with the PVM is not simply mediated via a single molecule but supported by a complex of PVM proteins. Actually, we previously reported that the interaction of ZP1 and ZP3 (Ohtsuki et al 2004, Sasanami et al 2006 as well as that of ZP2 and ZP3 (Kinoshita et al 2010) play a role in the formation of the PVM during follicular development in quail. Moreover, we found that the sperm acrosin contains disulfide-bonded threedimensional arrangement with a modification of sugar moiety in the molecule, though a role of these structures for the sperm-egg interaction in fertilization remains to be studied (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not pursue the discrepancy of the results between the dot blot assay and far-western blotting, we assume that the interaction of the 45 kDa acrosin with the PVM is not simply mediated via a single molecule but supported by a complex of PVM proteins. Actually, we previously reported that the interaction of ZP1 and ZP3 (Ohtsuki et al 2004, Sasanami et al 2006 as well as that of ZP2 and ZP3 (Kinoshita et al 2010) play a role in the formation of the PVM during follicular development in quail. Moreover, we found that the sperm acrosin contains disulfide-bonded threedimensional arrangement with a modification of sugar moiety in the molecule, though a role of these structures for the sperm-egg interaction in fertilization remains to be studied (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Although the cause of this phenomenon is not clear, there is a possibility that the ZP proteins are responsible. ZP2 is expressed in the oocyte of immature follicles and exists in the pvm as a minor component in Japanese quail (Kinoshita et al, 2010). ZP2 in the chicken also accumulates in the egg envelope of immature oocytes but it stays behind in the germinal disk region even after the follicle grows to the largest (Nishio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To observe the effect of anti-ZPs antibodies, the pvm was added into a tube containing either anti-ZP1 raised against the synthetic N-terminal peptide of ZP1 (Ohtsuki et al, 2004), anti-ZP2 raised against bacterially expressed ZP2 ( Kinoshita et al, 2010), anti-ZP3 raised against purified ZP3 from the pvm (Sasanami et al, 2002), anti-ZP4 raised against bacterially expressed ZP4 (Serizawa et al, 2011), anti-ZPD raised against bacterially expressed ZPD (Sato et al, 2009) or normal rabbit serum diluted 1:200 with HBSS, and sperm suspension was then added at 1×10 7 sperm/ml. We previously demonstrated that sperm binding to the pvm could be evaluated by inhibiting sperm AR in the presence of pertussis toxin (PTX, Calbiochem, La Jolla, CA, USA) , therefore 2 μg/ml PTX was added to the reaction mixture during the sperm-pvm incubation to analyze the sperm-pvm binding.…”
Section: Semen Collection and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, it was reported that ZP2 also supports the sperm binding (Bleil et al, 1988), and the structural change of the ZP2 as a result of limited digestion by the cortical granule protease protects the polyspermic fertilization (Burkart et al, 2012). In birds, ZP2 is expressed in the oocyte of immature follicles and exists in the pvm as a minor component (Kinoshita et al, 2010). Very recently, Nishio and colleagues demonstrated that ZP2 in the chicken accumulates in the egg envelope of immature oocytes and remains in the germinal disk region of the mature egg (Nishio et al, 2014).…”
Section: Sperm-egg Bindingmentioning
confidence: 99%